Maintenance Strategy Optimization for Auto Assembly Lever Holder Machine using Black-Box Approach - Lestari, Dewi Ayu; Herwanto, Dene; Sulaeman, Benyamine; Andini, Dian (Jurnal Serambi Engineering, 2026)
A manufacturing company that produces automotive components has recorded the auto assembly lever holder machine as the automatic machine with the highest failure frequency throughout 2024. This condition disrupts the smooth operation of the production process and results in decreased production output, often failing to meet company targets. In response to this situation, this study was conducted to estimate the reliability and optimize the maintenance policy of the auto assembly lever holder machine. The study employed a black-box failure modelling approach. A probabilistic approach was also applied by utilizing Weibull distribution properties to estimate system reliability and optimize the machine's maintenance strategy. Based on the conducted analysis, the machine has a cumulative failure probability of over 50% at 300 operating hours, indicating a high tendency for failure. The optimization of the maintenance policy considered both the periodic replacement policy and repair count policy. The optimized maintenance policy for the auto assembly lever holder machine recommends preventive maintenance every 522.305 hours at a lower maintenance cost of Rp 20,680 per hour. Replacement actions are only applied to the critical component. These findings provide a data-driven basis for optimizing machine maintenance strategies and reducing unplanned downtime, thereby improving machine reliability and productivity.